Associations between feelings of social anxiety and emotion perception. (June 2018) - Lynn, Spencer K.; Bui, Eric; Hoeppner, Susanne S.; O'Day, Emily B.; Palitz, Sophie A.; Barrett, Lisa Feldman; Simon, Naomi M.
Abstract: Background: Abnormally biased perceptual judgment is a feature of many psychiatric disorders. Thus, individuals with social anxiety disorder are biased to recall or interpret social events negatively. Cognitive behavioral therapy addresses such bias by teaching patients, via verbal instruction, to become aware of and change pathological misjudgment. The present study examined whether targeting verbal instruction to specific decision parameters that influence perceptual judgment may affect changes in anger perception. Method: We used a signal detection framework to decompose anger perception into three decision parameters (base rate of encountering anger vs. no-anger, payoff for correct vs. incorrect categorization of face stimuli, and perceptual similarity of angry vs. not-angry facial expressions). We created brief verbal instructions that emphasized each parameter separately. Participants with social anxiety disorder, generalized anxiety disorder, and healthy controls, were assigned to one of the three instruction conditions. We compared anger perception pre- vs. post-instruction. Results: Base rate and payoff instructions affected response bias over and above practice effects, across the three groups. There was no interaction with diagnosis. Discussion: The ability to target specific decision parameters that underlie perceptual judgment suggests that cognitive behavioral therapy might be improved by tailoring it to patients' individual parameter "estimation" deficits. Highlights: Perceptual judgments are made under perceptual uncertainty and economic risk. Participants completed a series of conservatively-biased emotion judgment tasks. A small amount of social anxiety was associated with the best response bias. Low and high extremes of social anxiety were associated with overly liberal bias.